Penerapan Budaya 5S Sebagai Penguatan Karakter Di SMK Muhammadiyah 1 Wates - Dinda Azzahra; Lail Syagheta Lifeaningrum; Farid Setiawan (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
This research aims to provide an overview of the implementation of the 5S culture (smile, greeting, greeting, politeness) and educators' methods for getting used to it. The targets of this research were students at SMK Muhammadiyah 1 Wates. This type of research uses qualitative research to describe actual school cultural behavior. The data sources in this research are class teachers, religion teachers, and school principals. This research collection technique is through observation, interviews and documentation. The results of this research reveal that the implementation of 5S school culture and the role of teachers in implementing it takes the form of routine activities, modeling, conditioning, habituation, advice and supervision.